An Antimicrobial and Antifibrotic Coating for Implantable Biosensors - Sofia Wareham-Mathiassen; Pawan Jolly; Nandhinee Radha Shanmugam; Badrinath Jagannath; Pranav Prabhala; Yunhao Zhai; Alican Ozkan; Arash Naziripour; Rohini Singh; Henrik Bengtsson; Thomas Bjarnsholt; Donald E. Ingber (Biosensors)
Biofouling and foreign body responses have deleterious effects on the functionality and longevity of implantable biosensors, seriously impeding their implementation for long-term monitoring. Here, we describe a nanocomposite coating composed of a cross-linked lattice of bovine serum albumin and pentaamine-functionalized reduced graphene that is covalently coupled to antibody ligands for analyte detection as well as antibiotic drugs (gentamicin or ceftriaxone), which actively combats biofouling while retaining high electroconductivity and excellent electrochemical immunosensor behavior. Sensors overlaid with this coating inhibit the proliferation of Pseudomonas aeruginosa bacteria and adhesion of primary human fibroblasts while not having any significant effects on fibroblast viability or on the immune function of primary human monocytes. Under these conditions, the sensor maintains its electrochemical stability for at least 3 weeks after exposure to soluble proteins that interfere with the activity of uncoated sensors. Proof-of-concept for the coating’s applicability is demonstrated by integrating the antimicrobial coating within an immunosensor and demonstrating the detection of cytokines in both culture medium and complex human plasma. This new coating technology holds the potential to substantially increase the lifespan of implanted biosensors and widen their application areas, potentially enabling continuous monitoring of analytes in complex biofluids for weeks in vivo.